A protein-free extender for semen cryopreservation in wood bison - Yang, Steve 1992- (2018)
Animal proteins are a common constituent of semen extenders to protect sperm from cold shock but they raise issues concerning biosecurity and undefined composition. The purpose of this study was to determine if cholesterol-cyclodextrin (CC) can be used to replace egg yolk from extenders in cryopreservation of beef and bison semen. In initial study, semen was collected from wood bison and frozen in either conventional egg yolk (TEYG) or CC Tris-glycerol (CC-TG; 2 mg CC/mL semen) extender. Sperm motion characteristics, i.e., total motility, progressive motility, curvilinear velocity (VCL), average path velocity and straight-line velocity were determined using computer-assisted sperm analysis. There were no difference in sperm motion parameters other than VCL. Following fixed-time artificial insemination (FTAI), TEYG semen yielded 9/21 (43%) pregnancy rates while no bison conceived with 2 mg CC-TG semen. Concentration of CC used and bison species specific problems were suspected for lack of pregnancies. In the second study, three experiments were conducted with lowered concentrations of CC in both beef and wood bison to investigate the issue of failure to conceive. In Experiment 1, semen was collected from beef bulls and frozen in TEYG, 1 mg CC-TG, or 2 mg CC-TG extender. Pregnancy rates were 20/40 (50%), 20/41 (49%), and 5/39 (13%) for TEYG, 1 mg CC-TG and 2 mg CC-TG semen following FTAI of Hereford-cross cows, respectively. In Experiment 2, 0.5 mg CC-TG extender was tested in beef cows. Pregnancy rates of 25/46 (54%), 26/46 (57%) and 13/40 (33%) for TEYG, 0.5 CC-TG, and 1 mg CC-TG semen following FTAI of Hereford-cross cows, respectively. In Experiment 3, lower concentrations of CC were tested in wood bison. Pregnancy rate of 6/11 (55%) and 4/11 (36%) were achieved for TEYG and 1 mg CC-TG semen, respectively. These were the first reports of pregnancies in bison and beef cows using CC-TG extender. The overall results of the study demonstrated that CC can be used to effectively replace egg yolk from semen extenders ...